Green entrepreneurship in India - Nayak, YD; Sahoo, AP (International Journal of Agricultural Research, Innovation and Technology, 2022)
Entrepreneurs are credited with playing a key role in wealth creation and economic development. There has been enough focus of empirical literature on linking entrepreneurship and employment generation, reducing income disparity and contributing to balanced regional development. However, the environment catastrophe, world is facing, has made it imminent for the business to find new ways of doing business. Green Entrepreneurship, however nascent, provides a gleam of hope to in the direction of sustainable development. Growing consumer awareness and preference towards environmentally friendly products has also made embedding green concepts in business models a source of competitive advantage. This study is exploratory in nature as it offers insights into the emergence of the concept of green entrepreneurship and its role in the Indian context. Based on available literature, the study proposes a conceptual model explaining a link between various social, environmental and institutional factors and green entrepreneurship, leading to sustainable development. The study also explores current green entrepreneurship scenario in the light of opportunities and challenges by presenting the case studies of successful green ventures in India. Int. J. Agril. Res. Innov. Tech. 11(2): 72-75, Dec 2021